DESIGNING SUPPLEMENTARY READING E-WORKSHEET BASED ON SDGs (SUSTAINABLE DEVELOPMENT GOALS) FOR TENTH-GRADE STUDENTS AT SMAN 3 TARAKAN - Alya, Nurul Rezky; Arifin, Arifin; Rafiqa, Syarifa (Universitas Borneo Tarakan, 2023)
This study aims to design a supplemental reading e-worksheet based on SDGs (sustainable development goals) with adequate materials and an attractive design for the tenth-grade students at SMAN 3 Tarakan. This research and development research used the ADDIE Model, which consisted of five stages: (1) Analysis, (2) Design, (3) Development, (4) Implementation, and (5) Evaluation. The subjects of the research were 35 students of Class X-E in SMAN 3 Tarakan. This research included two expert validators: the media expert and material expert validators. The results indicated that validation by the material expert was 86% included the excellent category and the material expert were 100% with the very good type for the supplemental reading e-worksheet based on SDGs (sustainable development goals). The evaluation test results were divided into two: the small evaluation test was 81% (good category), and the field evaluation test was 83% (suitable type). The research and development results of the Supplementary Reading E-Worksheet based on SDGs (Sustainable Development Goals) for Tenth Grade students at SMAN 3 Tarakan are feasible for use in English learning.Â